Impact of Investors’ Attention on the Global Stock Market : A Bibliometric Analysis - Lohan, Sheenam; Sidhu, Arpit; Kakran, Shubham (Indian Journal of Finance, 2023)
Purpose: The stock market is a highly dynamic financial marketplace that drives economic progress. This study employed bibliometric analysis, using tools like Biblioshiny and VOSviewer, to execute quantitative analysis on research papers around the stock market in terms of investor attention. It improved the literature review’s quality by analyzing 632 research papers from the Scopus database. Design/Methodology/Approach: The selected papers from 1994 to 2022 were reviewed and analyzed. A conceptual model identified significant themes, while a thematic map provided a comprehensive visual representation of the interconnections. Results: The analysis yielded noteworthy findings, highlighting a significant surge in academic publications. Most of the research regarding investor attention and the stock market has been concentrated in China, the UK, the USA, and Australia, indicating this topic’s global relevance. Among the identified high-frequency keywords, investor attention, investment, and attention stood out as prominent themes within the literature. Finance Research Letters and Pacific-Basin Finance Journal were identified as influential publication outlets. Originality/Value: This research introduced novel bibliometric analysis techniques, providing robust insights into the stock market concerning investor’s attention. Integrating a conceptual model and thematic map enhanced understanding and contributed innovatively to the field. Practical Implications: The study offered regulatory implications, aiding policymakers in understanding the stock market concerning investor’s attention. Practitioners could utilize the findings for informed decision-making in stock companies and gain insights into emerging research trends.